Potensi Ekstrak Etanol Herba Binara (Artemisia vulgaris L.) sebagai Antibakteri Staphylococcus aureus - Arifin Putra Zai; Samran; Aminah Syarifuddin; Cucu Arum Dwi Cahya (Yayasan Penelitian dan Inovasi Sumatera, 2023)
Background: Herb Binara has potential as an antimicrobial against Staphylococcus aureus, because this plant has several compounds that have medicinal properties, including: alkaloids, saponins and flavonoids. This compound can act as a natural antibiotic. Objective: The study was aimed at finding out whether Binara extract has antibacterial potential. Methods: The study was carried out using a disc diffusion system to assess the antibacterial potential of Binara herbal extract. Antibacterial potency is based on the area of obstruction around the disc. The study used four extract concentrations (20, 40, 60, and 80%), clindamycin, and DMSO. Results: Test results for the antibacterial potential of the ethanol extract of Binara herb at a concentration of 80; 60; 40; and 20% each show the resistance area is 12.90; 10.50; 9.00; and 8.10 mm. Conclusion: Binara herb ethanol extract has potential as an antibacterial with moderate to strong potency criteria